Analyses of GWAS and Sub‐Threshold Loci Lead to the Discovery of Dendrite Development and Morphology Dysfunction Underlying Schizophrenia Genetic Risk - Rui Chen; Benjamin Siciliano; Quan Wang; Chongchong Xu; Qiang Wei; Hai Yang; James S Sutcliffe; Yi Jiang; Ying Ji; Chunyu Liu; Feixiong Cheng; Edwin H Cook; et al. (Advanced Science, 2025)
Abstract Schizophrenia (SCZ) is highly polygenic, and its biological underpinnings remain unclear. In this study, a cost‐effective strategy of including sub‐threshold GWAS (subGWAS) loci (i.e., 5 × 10−8 < P ≤ 10−6) in analysis is explored to increase the inference power of novel pathways. A total of 180 subGWAS loci are identified from SCZ GWAS studies and are shown to contain substantial true genetic association signals. By jointly modeling GWAS (sigGWAS) and subGWAS loci, 304 high‐confidence risk genes (HRGs) are identified, as well as a novel category of biological processes detected only in subGWAS loci, i.e., dendrite development and morphogenesis (DDM). Two candidate DDM genes (CUL7 and DCC), whose risk alleles in GWAS are associated with increased expression, are examined, and it is observed that upregulation of these genes leads to reduced neurite length. It is further revealed that the DDM genes lead to disrupted regulatory programs of the transcription factors CUX1/2 and NEUROD1. Collectively, the study identifies DDM as a novel biological process in SCZ susceptibility, with particular implications for DCC‐ and CUL7‐mediated alterations in neurite development and reveals regulatory programs involved in perturbation of the two candidate genes.